BRITISH RURAL SETTLEMENTS IN THE HINTERLAND OF CONURBATIONS - A CLASSIFICATION - Donnelly, P; Harper, S (1987)
Various techniques of cluster analysis are applied to 125 civil parishes in southern Hampshire and 55 civil parishes in southern Staffordshire. Despite the differing infrastructure, the analysis identifies within both a similar spectrum of settlements defined by size, tenancy,and age structure: small Established villages with a high proportion of tied and rented property, a high percentage of village workers and typically an old age profile; large Metropolitan villages which are dominated by owner occupied property, and possessing a younger age profile and a high proportion of commuters; and between these two extremes, Uniform villages, which are average in size with a tenure system balanced between tied and privately rented, local authority, and owner occupied property, some commuters and a balanced or slightly older than average age profile. Concludes that owing to the current planning policy of both these counties, such a spectrum is likely to remain relatively stable. -from Authors